War Shocks on Export Lanes: Is World Trade Performance Slowing Down? - Hotsawadi, Hotsawadi; Veronica Gea, Imelda; Nuzulia, Nuzulia (www.bsi.ac.id, 2025)
In recent years, geopolitical tensions and armed conflicts have had a significant impact on the global trading order. For this reason, this study aims to analyze the relationship between international armed conflict and estimated export performance using the ARDL Panel Model. The results of the estimation using the ARDL Panel Model show that military conflicts have a significant negative impact on export performance in the long run, reflecting the vulnerability of international trade to geopolitical instability. On the other hand, real GDP, population, and investment exhibit significant positive influences that enhance production capacity, expand markets, and improve export competitiveness in the global market. These findings suggest that domestic factors that support economic growth play a crucial role in maintaining export resilience, despite external challenges such as military conflicts and fluctuations in exchange rates. The real exchange rate has been shown to have a negative impact, suggesting that currency appreciation can erode the competitiveness of export prices. Therefore, exchange rate stability is a crucial factor that must be maintained